2016
DOI: 10.1103/physrevfluids.1.014201
|View full text |Cite
|
Sign up to set email alerts
|

Dense spray evaporation as a mixing process

Abstract: We explore the processes by which a dense set of small liquid droplets (a spray) evaporates in a dry, stirred gas phase. A dense spray of micron-sized liquid (water or ethanol) droplets is formed in air by a pneumatic atomizer in a closed chamber. The spray is conveyed in ambient air as a plume whose extension depends on the relative humidity of the diluting medium. Standard shear instabilities develop at the plume edge, forming the stretched lamellar structures familiar with passive scalars. Unlike passive sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
30
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 35 publications
(43 reference statements)
3
30
0
2
Order By: Relevance
“…is the Spalding mass number, where Y d is the mass fraction of water vapor at the droplet surface and Y p is the mass fraction of water vapor in the surrounding puff. Under the assumption that N u and B m are nearly constant for small droplets, the above equation can be integrated [24] to obtain the following law (mapping) for the evolution of the droplet:…”
Section: Droplet Size Controlled By Evaporationmentioning
confidence: 99%
“…is the Spalding mass number, where Y d is the mass fraction of water vapor at the droplet surface and Y p is the mass fraction of water vapor in the surrounding puff. Under the assumption that N u and B m are nearly constant for small droplets, the above equation can be integrated [24] to obtain the following law (mapping) for the evolution of the droplet:…”
Section: Droplet Size Controlled By Evaporationmentioning
confidence: 99%
“…Therefore, given our past experience with various types of experiments with mono-dispersed droplet generators and after careful consideration, we decided to use a commercial atomizer which produces a polydispersed droplet size distribution that is typical to injectors used in several combustion applications, and can be quantified without evaporation, and we use this as a reference to evaluate the evolution of the evaporation rate in the spray. However, it is also noted that, earlier, droplet evaporation experiments in sprays with nearly mono-sized droplets (around 10 µm) have been reported (for instance, see Rivas & Villermaux 2016). Use of such sprays has some advantages, since it allows for well-defined boundary conditions for droplet sizes to assist comparison with spray simulations.…”
Section: Flow and Optical Arrangementmentioning
confidence: 99%
“…the regression rate of the droplet surface may vary nonlinearly with time. For instance, in their experiments studying the evaporation and mixing processes in a dense spray plume, Rivas & Villermaux (2016) and Villermaux et al (2017) demonstrated that the lifetime of an individual droplet embedded in a cloud of droplets is much larger than predicted by the conventional d 2 -law for a single drop evaporating in a quiescent environment. In a turbulent spray, due to the wide range of the droplet size distribution in sprays, different dynamic behaviour of droplet dispersion and interaction with the surrounding gas leads to formation of instantaneous clusters of droplets in sprays (Zimmer et al 2003;Lian, Charalampous & Hardalupas 2013).…”
mentioning
confidence: 99%
“…Закономерности испарения капель играют важную роль при решении ряда прикладных задач для теплотехнических систем и технологических процессов [1,2]. Различным аспектам нагрева и испарения отдельных капель и капельных систем посвящены многочисленные публикации, связанные с численным моделированием [3][4][5][6][7] и экспериментальными исследованиями [8][9][10][11][12][13][14] процесса испарения. Большинство экспериментальных результатов исследования скорости испарения капель жидкости получено при их нагреве в условиях кондуктивного, конвективного или комбинированного радиационноконвективного теплообмена [2,8,14].…”
unclassified
“…Большинство экспериментальных результатов исследования скорости испарения капель жидкости получено при их нагреве в условиях кондуктивного, конвективного или комбинированного радиационноконвективного теплообмена [2,8,14]. Скорость испарения капель определялась при их нагреве на твердой подложке [11], в условиях обдува неподвижной капли высокотемпературным потоком воздуха [2,[8][9][10], при движении капель через газообразные продукты сгорания [2,[12][13][14] или через полый цилиндрический нагреватель [2,12].…”
unclassified